PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DIVIDEN DAN UMUR PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Giovani Anggasta, Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to determine the effect of firm size, profitability, dividend, and firm age on firm value. The research sample used 45 manufacturing companies listed on the Indonesia Stock Exchange during the period 2015-2017. Price to book value (PBV) is used to proxy firm value and statistical analysis which is performed using multiple regression analysis to test the hypothesis. The results of this analysis indicate that firm size, dividend, and firm age do not have effect on firm value, while profitability has positive effect on firm value.